2018
DOI: 10.15611/aoe.2018.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Technical analysis gives you courage, but not money-von the relationship between technical analisys usage, overconfidence and investment performance

Abstract: This paper investigates the psychological background of the use of technical analysis in the financial markets. Such a background may give additional explanations to the popularity and common usage of technical analysis as an investment decision tool. This popularity is puzzling due to the missing theoretical and scientific background of technical analysis and the contradictory empirical evidence on its effectiveness. We postulate that overconfidence (regardless of its manifestation: calibration, better than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Information overload occurs "when the information processing demands on an individual's time to perform interactions and internal calculations exceed the supply or capacity of time available for such processing" (Schick, Gorden, Haka, 1990, p. 199). Trading is done in an environment characterised by strong information load and it has been proved that traders exhibit an illusion of control in their investment decisions (Fenton-O'Creevy, Nicholson, Soane, Willman, 2003;Kubińska et al, 2018). We hypothesise that information overload causes an illusion of control, and sought to verify this in an experimental study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Information overload occurs "when the information processing demands on an individual's time to perform interactions and internal calculations exceed the supply or capacity of time available for such processing" (Schick, Gorden, Haka, 1990, p. 199). Trading is done in an environment characterised by strong information load and it has been proved that traders exhibit an illusion of control in their investment decisions (Fenton-O'Creevy, Nicholson, Soane, Willman, 2003;Kubińska et al, 2018). We hypothesise that information overload causes an illusion of control, and sought to verify this in an experimental study.…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that overconfidence in the form of the illusion of control is a very strong bias among financial market professionals. This type of bias occurs more frequently with technical analysis usage (Kubińska, Czupryna, Markiewicz, Czekaj, 2018). Financial market professionals are influenced by the increasing amount of information they are confronted by, with enormous amounts of news that are not fundamental information but just a 'noise' (Black, 1986), leading to informational overload (Chewning, Harrell, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The weak form of the efficient market hypothesis suggests that the current price of a security reflects all currently available information, including previous prices (EF Fama, 1970). Such skepticism regarding TA is justified, studies showing that its use is not profitable (Aronson, 2011;Hsu, Hsu, & Kuan, 2010;Kubińska, Czupryna, Markiewicz, & Czekaj, 2018). More specifically, the idea that TA can generate extra profits is often lacking in terms of statistically significant evidence, and, even where such evidence is presented, it can easily be explained by data mining bias or post factum analysis.…”
mentioning
confidence: 99%
“…In addition to the issue of which mechanism underlies chartists' faith in TA, a no less important issue is that relating to the method's psychological concomitants. If TA does not result in systematic extra profits for its adherents (Kubińska et al, 2018), what benefits does it bring them? It must provide something since time and resources are invested in learning its techniques and in conducting analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation